The science of winning series - Sport psychology
Zusammenfassungen zu sportpsychologischen Forschungsvorhaben des Sportrates von Singapur zu folgenden Themen: Psychology in Sports Injury Psychology in Sports Injury Delivery of Sport Psychology Services to the Singapore Olympic Team Prior to and During the Olympics Imagery-based Intervention Techniques with Competitive Athletes Effects of Music on Vividness of Movement Imagery